Lightning myths and beliefs in South Africa: Their effect on personal safety - Trengove, Estelle (My University, 2013)
Every year, lightning kills and injures people and animals and damages property in South Africa. Rural people who work outdoors tending the land or herding animals are particularly vulnerable to lightning strikes. A lightning awareness effort might help to reduce the annual number of lightning deaths in South Africa. This thesis describes an attempt at understanding southern African traditional myths and beliefs related to lightning and to examine how these could inform lightning awareness and education. Lightning awareness efforts in other countries are assessed in terms of their suitability with respect to South Africa. Finally, a model for a mobile lightning warning and awareness is proposed based on the current African mobile culture. Mobile telephones have created a revolution in communications in Africa. Millions of people living in rural areas never had any infrastructure: no fixed-line telephone infrastructure, not even electrical power, hence no computer communications, but mobile telephones and the short message service (SMS) have changed that. The proposal suggests leveraging the exponential growth of a mobile culture in Africa and gives a high-level outline of what such a system might look like.